Memories of Miriam Álvarez Brenes Presentation of the book by Alejandra Chaverri - Chaverri Alvarez, Alejandra (2017)
Presentation of the book by the compiler. In this presentation the origin and reflection of The Memories of Miriam Álvarez Brenes is collected.